Pengaruh Stres Kerja dan Organizational Behavior (OBC) Terhadap Kinerja Personel Satlantas Aceh Besar dalam Menekan Angka Kecelakaan Lalu Lintas - Anas, Hanifah; Earlyanti, Novi Indah; Prianggono, Jarot; Prianggono, Halimah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
In an effort to reduce the number of work accidents, Satlantas members as the responsible party need to maintain their performance in the field. However, in reality, performance can be influenced by other variables such as work stress and OCB. This will affect the results and quality of performance carried out. The purpose of this study was to determine the relationship and influence between two variables, namely work stress (X1) and OCB (X2) on the performance (Y) of Satlantas Aceh Besar members in reducing traffic accidents. This study is a study with a quantitative approach using a survey method. Data collection was carried out by distributing questionnaires containing 50 statements to 44 respondents of Satlantas Aceh Besar. Data analysis in this study used multiple linear regression, which produced the equation Ŷ = a + b1X1 + b2X2 + e where work stress and performance have a negative relationship direction with a coefficient value of -0.247, while the tcount value> ttable (-2.020) which means H0 is rejected. Then the results of the OCB t-test on performance have a t-value of 7.465 which is greater than the t-table of 2.020 so that H0 is accepted and OCB has an effect on performance with an F-value of 52.182 greater than the Ftable of 3.226 meaning that H0 is accepted which means that work stress and OCB together have an effect on performance. Then the results of the determination coefficient are known to be 0.718 which means that work stress and OCB have an effect on performance of 71.8%. From these results it can be concluded that work stress does not have a significant effect on member performance, while OCB has a significant effect on member performance and OCB with work stress together affect member performance.